Rigenerazione e politiche giovanili: quale collegamento per rispondere alle attuali sfide sociali? Un'analisi qualitativa del Centro giovani Smart Lab di Rovereto - Fiorenza, Miriam (FrancoAngeli, 2022)
The book presents a study about synergies between urban regeneration and welfare policies, created in an important municipality of Trentino (Italy), to answer the social challenges of the territory. The text reviews the literature on regeneration, welfare, and youth policies and presents the survey techniques used for the study of the Smart Lab youth center in Rovereto. It addresses the issue of culture as a vehicle for innovation that leads to social and economic results that are difficult to recognize, even for the direct users. The research helped to encapsulate this development action and to construct a definition of the center by the users themselves.